Rancang Bangun Alat Roll Press untuk Mengolah Batang Tanaman Rumput Payung (Cyperus Alternifolius) menjadi Serat Bahan Baku Komposit - Murdiyanto, Danang; Redationo, Nereus Tugur (Jurnal Rekayasa Mesin, 2015)
Composite material could be developed into new material that would be useful for many interests. Fiber as composite raw material must be given pretreatment to improve the quality of composite. In this research, raw material for the composite was umbrella grass (Cyperus Alternifolius). A tool was designed to facilitate the processes of rolling or pressing, or abbreviated as roll press. Indeed, the design of roll press was preceded by designing the construction section that involved shaft, transmission system, bearing, pulley belt, and driver motor to move the roll. Result of rolling must be suitable for processing umbrella grass into the fiber of composite raw material. Testing was conduced to examine the work of the tool against the stalk of umbrella grass. Two testing was considered. First was testing against the variation of loads, which involved 10kg, 12kg and 14kg. Second test was against the variation of roll rotation at 160rpm, 197rpm and 280 rpm. Result of both tests provided specific fiber derived from umbrella grass that would be compatible to be composite material. Some results of research were indicated. Main drive motor was Â½ PK with rotation (n1) = 1430rpm. Pulley diameter (d1) was 75mm. Reducer system was signified by n2 = 831rpm and d2 = 129mm, and if d3 = 59mm was used, the outcome was n4 = 160rpm with d4 = 307mm. In case of bearing, its sliding moment was 0.309N.mm and tangent force was 2.06N. The frame of roll press tool was designed at the dimension of length x wide x height = 600mm x 320mm x 1200mm. The best parameter was 160rpm with load force of 10kg. By taking account all these results, it could be said that the result of roll press processing had successfully produced the fiber from umbrella grass into the suitable raw material for the composite.